Organisational inhibition and promotion of flexible working in digitalised work environments - Anja-Kristin Abendroth; Mareike Reimann (New Technology, Work and Employment, 2023)
Work-related use of digital information and communication technology (ICT) is not restricted to specific working sites and times. For employees, this can involve opportunities for flexible working, that is, having control over when and where to work. Applying an organisational comparative perspective, we examined whether adherence to the ideal worker norm inhibits and adherence to family-friendliness promotes flexible working as a consequence of ICT use. Linked employer–employee survey data from large German work organisations revealed that employees worked more flexibly in time and place due to work-related ICT use when supervisory work-life support was common. Mixed evidence is provided for the prevalence of ideal worker norm expectations. We conclude that work-life support in the organisation is a required complementary practice of flexible working for employees, promoting its dissemination.
Keywords: 330; digitalisation; employment relations; flexible working; ICT; job quality; organisations; technology; work–life support